2007
DOI: 10.1007/s10649-006-9045-1
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Elementary Teachers’ Voices Describe How Their Teacher Motivated Them to do Mathematics

Abstract: In this study, data in the form of (preservice teacher) student voices taken from mathematical autobiographies, written at the beginning of the semester, and end-ofsemester reflections, were analyzed in order to examine why preservice elementary school teachers were highly motivated in a social constructivist mathematics course in which the teacher emphasized mastery goals. The findings suggest that students entered the course with a wide variety of feelings about mathematics and their own mathematical ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 20 publications
1
12
0
4
Order By: Relevance
“…However, comments throughout indicated their new understanding of allowing open exploration and providing opportunities for students to make meaning out of math concepts. Harkness, D'Ambrosio, and Morrone (2007) found providing preservice teachers with the opportunity to engage in this constructivist type of learning can change how they think about and view math and learning math, refocusing on the "why" of math rather than math "performance" (p. 249). This type of teaching aligns with current ideas about best instructional practices, as well as the expectations of the Common Core State Standards, and may better prepare teachers for future classroom work.…”
Section: Further Reflection and Continuing Questionsmentioning
confidence: 99%
“…However, comments throughout indicated their new understanding of allowing open exploration and providing opportunities for students to make meaning out of math concepts. Harkness, D'Ambrosio, and Morrone (2007) found providing preservice teachers with the opportunity to engage in this constructivist type of learning can change how they think about and view math and learning math, refocusing on the "why" of math rather than math "performance" (p. 249). This type of teaching aligns with current ideas about best instructional practices, as well as the expectations of the Common Core State Standards, and may better prepare teachers for future classroom work.…”
Section: Further Reflection and Continuing Questionsmentioning
confidence: 99%
“…As reported in Harkness et al (2007), the preservice teachers' mathematical autobiographies shed light on their mathematical self-concepts. At the beginning of the semester the preservice teachers were asked to describe their school experiences with mathematics and the findings indicated that they entered Problem Solving with a wide variety of feelings about mathematics and their own mathematical skills.…”
Section: The Mathematics Coursementioning
confidence: 90%
“…The study reported here is the third in a series of research articles (Harkness, D'Ambrosio, & Morrone 2007;Morrone, Harkness, D'Ambrosio, & Caulfield 2004) about the teaching practices of the same university professor, Sheila, and the mathematics course, Problem Solving, she taught for preservice elementary teachers. The preservice teachers reported that they were motivated and that Sheila made learning goals salient (Harkness et al 2007;Morrone et al 2004).…”
Section: Connection To Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations